PENGARUH MODAL AWAL, LOKASI USAHA, DAN LAMA USAHA TERHADAP PERBEDAAN PENDAPATAN USAHA MIKRO KECIL MENENGAH (UMKM) KECAMATAN UJUNG BATU DAN TANDUN - Anggi Elina Anggi; Rina Febrinova; Defidelwina (SUNGKAI, 2026)
MSMEs in Ujung Batu District tend to have higher incomes than Tandun District. This difference is indirectly suspected to be influenced by three main factors, namely the initial capital, the length of the business, and the location of the business. Therefore, this study aims to analyze the factors that affect the differences in the income of culinary MSMEs in Ujung Batu and Tandun Districts, Rokan Hulu Regency. The main factors studied include initial capital, business location, and length of business. This study uses a quantitative method with data collection techniques through surveys, interviews guided by questionnaires, and documentation with a sample of 98 business actors. Data analysis was carried out by independent sample t-test, and multiple linear regression analysis. The results of the study showed that there was a significant difference in income between culinary MSMEs in Ujung Batu and Tandun Districts, where Ujung Batu had an average income of IDR 26,765,306 higher than Tandun with an income of IDR 17,903,061. In addition, the results of the regression test revealed differences in variables that affected income, where in Ujung Batu the significant variables were Initial Capital (X1) and Duration of Business (X3). while in Tandun the significant influence is Initial Capital (X1) and Business Location (X2). This study recommends that Tandun MSME actors can increase initial capital so that the MSMEs that are run can sell competitive products and it is recommended that Tandun MSMEs can choose strategic business locations, for example, close to crowds and have a large parking lot.